Effects of Cloud-based Gamified Instruction Integrating Peer Assessment on Primary Students’ English Writing and Critical Thinking - Norphealey Eang; Sirirat Petsangsri; John Morris (LEARN Journal : Language Education and Acquisition Research Network, 2025)
English writing and critical thinking are not only fundamental to academic success but also play a crucial role for the holistic development of primary students. This study investigated the effects of a cloud-based gamified instruction integrating peer assessment on primary student English writing and critical thinking. A pre- and post-test with a delayed pos-test research design was used; thirty-five grade sixth students participated in the study. The research instruments included writing and critical thinking tests. The data were analyzed using repeated measures ANOVA. There was a significant improvement writing from a pre-test through and post-test and delayed post-test (F = 853.76, p < 0.001). The F-value indicated a significant difference between pre- and post-test, but there was little difference between post- and delayed post-tests. The high effect size (η² = 0.96) confirmed the effectiveness of the intervention on writing. Similarly, analysis also indicated a significant effect the intervention on the critical thinking improvement over time (F = 632.89, p < 0.001). The high effect size (η² = 0.95) emphasized the practical significance of the improvements across the three time points. This confirmed the positive effects of the cloud-based gamified instructional model on writing and critical thinking.
Keywords: Education and Learning Interventions; Educational Systems and Policies; Education, Safety, and Science Studies